Acoustic Analysis of the Speech of the Hearing-impaired - Rajanikanth B.R (Journal of All India Institute of Speech and Hearing, 1970)
The speech- of the deaf differs from that of normals in all regards. In all the studies of the speech of the hearing-impaired, attention is drawn tothe fact that, to a greater or lesser degree, the hearing-impaired individuals do not produce speech as well as those who hear.